Cultural heritage in international investment law and arbitration - Vadi, Valentina
"Can states adopt protectionist cultural policies? What are the limits, if any, to state intervention in cultural matters? A wide variety of cultural policies may interfere with foreign investments, and a tension therefore exists between the cultural policies of the host state and investment treaty provisions. In some cases, foreign investors have claimed that cultural policies have negatively affected their investments, thereby amounting to a breach of the relevant investment treaty. This study maps the relevant investor-state arbitrations concerning cultural elements and shows that arbitrators have increasingly taken cultural concerns into consideration in deciding cases brought before them, eventually contributing to the coalescence of general principles of law demanding the prote